THE PROCESS OF PROVIDING THE POPULATION WITH HOUSING IN THE SYSTEM OF SOCIAL PROTECTION IN UZBEKISTAN. (In the case of the Fergana Valley, 2016-2020) - Rahmonov Elyor Abdullajonovich; Mukhsin Moydinovich Kholmatov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article analyzes the achievements of our Republic in the field of social protection on the basis of large-scale reforms implemented in recent years. In particular, the results of the work carried out in 2016-2020 on the provision of housing, which is one of the priorities of the process of social protection, are scientifically and theoretically highlighted.